PENGARUH KONFORMITAS TERHADAP KEDISIPLINAN ANGGOTA RESIMEN MAHASISWA DI SUMBAWA - Ahmad Mulyadi; Lukmanul Hakim (JURNAL PSIMAWA, 2021)
Conformity is a type of social behavior in which individuals change their attitude and behavior to conform to social norms. Discipline is the awareness and willingness of someone who obeys all company regulations and applicable social norms. The purpose of this study is to determine whether there is an effect of Conformity on the Discipline of Student Regiment Members in Sumbawa. This research uses descriptive quantitative approach, the sampling technique uses cluster random sampling. The sample in this study amounted to 100 members of the student Regiment. Research data is obtained using the research instrument in form of two scales namely Conformity scale and Discipline scale. Results showes that Conformity is affecting the Discipline of the Student Regimen Members in Sumbawa with value p = 0,000/p < 0,05 and R square of 0,559 Wich means that the higher the Conformity of the members of the Student Regiment, the higher the influence on Discipline. Conformity has an effect of 55,9% while the remaining 44,1% is influenced by other variables not examined in this study.